Myths and Realities of Rural Schools. The Voice of Families and Teachers - Raposo-Rivas, Manuela (2024)
Introduction. By invoking Shakespeare’s famous query, ‘to be or not to be, that is the question,’ this study examines rural schools by exploring the beliefs and myths surrounding them and contrasting these perceptions with the realities of daily life in 6 unitary rural schools located in the northwest of Spain. Aims. This study aims to listen to and shed light on the perspectives and feelings of families and teachers in rural schools with multi-grade classrooms. Method. Using a multiple case study design and triangulating qualitative instruments (photovoice, incomplete sentence prompts, and observation), we analyzed the evaluations and experiences of 76 families and 18 teachers concerning the context, the educational practice, and the internal sphere of rural schools. The data were processed through content analysis using ATLAS.ti 22 software, resulting in the identification of 8 categories and 3 dimensions: space and resources, coexistence, teaching and learning in rural schools. Results. The findings reveal several myths and idealizations held by teachers and families regarding the following aspects: the natural rural environment; facilities, infrastructures, resources, and services; coexistence; individualisation, multi-grade classrooms, and academic performance in rural schools. Conclusions. The study concluded that some of these myths do not align with the actual conditions of the studied environment. Rural schools can offer authentic, high-quality learning experiences on equal terms with other educational institutions, dependent on the mediation of the teaching teams that work in them. The study allows for reflection and provides information not only to visibility of rural schools and empower them but also to make decisions enable their educational improvement.